1990
DOI: 10.1016/0248-4900(90)90358-a
|View full text |Cite
|
Sign up to set email alerts
|

A ground‐based model to study the effects of weightlessness on lymphocytes

Abstract: The mitogenic response of human lymphocytes was found to be markedly reduced in weightlessness conditions as compared to normal gravity. One possible explanation is that due to the non-existent sedimentation in space the lymphocytes could not adhere and spread on a substratum. Thus, we investigated the effect of substratum adhesiveness on lymphocyte responsiveness by reducing and blocking cell adhesion with poly-HEMA in a simple on-ground system. Lymphocyte adhesiveness was assessed by measuring the proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…However, when we tried to increase the amount of cell-cell contact by increasing cell densities in the RWV, proliferation was not restored. Although some studies suggest that cell-substratum interaction is important to T cell activation [59], we found that PBMC activated with PHA in Teflon culture bags was unaffected. The ability of cells to interact with substratum may not be as important as the ability to interact with other cells.…”
Section: Discussionmentioning
confidence: 49%
“…However, when we tried to increase the amount of cell-cell contact by increasing cell densities in the RWV, proliferation was not restored. Although some studies suggest that cell-substratum interaction is important to T cell activation [59], we found that PBMC activated with PHA in Teflon culture bags was unaffected. The ability of cells to interact with substratum may not be as important as the ability to interact with other cells.…”
Section: Discussionmentioning
confidence: 49%
“…Likewise, under 1-g conditions, nonadherent cells of the type used in our experiments sediment to the floor of the culture container, which increases the possibility of cell to cell contact and mechanical interaction with the culture vessel, compared with cells in suspension, as would be the case for cells under microgravity. Although the cell types used in our experiments proliferate in an anchorage-independent manner, complete inhibition of attachment to the cell culture vessel has been reported to inhibit proliferation (32). In contrast, it is much less obvious how change in gravity could be directly perceived by a single cell.…”
Section: Discussionmentioning
confidence: 70%
“…The clinostat model system (clinorotation) is a ground‐based method for providing a vector‐averaged reduction in the apparent gravity on the cell culture (4, 5). Clinorotation of samples was performed at 37°C in 1.2 ml cryovials (Corning Glass Works, Corning N.Y.) filled to capacity.…”
Section: Methodsmentioning
confidence: 99%